Land Grabbing di Telukjambe Barat, Karawang, Jawa Barat dan Tautan Teoritiknya pada Karya David Harvey dan SMP Tjondronegoro - Abbas, Ria Renita; Soetarto, Endriatmo; Pandjaitan, Nurmala K; Satria, Arif (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
Regional developments in Karawang Regency, West Java have resulted in the marginalization of suburban communities. This marginalization occurs through the process of land grabbing or massive expropriation of land owned by suburban communities, which are none other than village communities that have occupied their lands for a long time. This article aims to contribute to two things. The first is to present an empirical description of the land grabbing process in suburban communities based on a case study in Telukjambe Barat, Karawang Regency, West Java. The second is to present a theoretical discussion to explain this land grabbing phenomenon by referring to the theoretical framework of David Harvey and S.M.P. Tjondronegoro. The research method used in this case study includes primary data obtained from in-depth observations and interviews with informants and is supported by secondary data derived from various research results and relevant documents. The results show that the expansion of urban capitalism in Telukjambe Barat is a spatial planning activity that is more directed at regional development with the presence of corporate power that has controlled space, conquered suburban community ownership, and has full power over space through land grabbing practices. The phenomenon of land grabbing in Telukjambe Barat was theoretically reinforced by S.M.P Tjondronegoro through the concept of “agrarian policy of agrarian denial” and David Harvey through the concept of accumulation by disposition.